Effect of Physical Education on Pupils' Motor Skill Development: A Case Study of Hamurwa Primary School Rubanda District. - Bagye, Jassy (Kabale University, 2025)
This study investigated the effect of physical education (PE) on pupils' motor skill development at Hamurwa Primary School, in Rubanda District. The study focused on the implications of PE on overall motor skill development, academic implication, and overall well-being. The research utilized a mixed-methods approach, combining quantitative surveys and qualitative interviews to assess the impact of structured PE programs on motor skills such as balance, agility, and coordination. Data was collected from 70 participants, including parents, teachers, and the head teacher, using questionnaires and interviews. The findings indicated that a large number (28.7%) stated that it leads to better motor control, agility, and strength, followed by (22.8%) of the respondents who stated improvement in running, jumping, and throwing, (18.5%) of the respondents stated that it brings an improvement in balance, hand-eye coordination and dexterity, (14.3%) of the respondents stated that it leads to improved cognitive functions such as memory, attention span and (10%) of the respondents stated improved children's engagement, while the rest (5.7%) of the respondents stated improvement in flexibility and physical fitness. The study concluded that integrating diverse physical activities into the curriculum supports both physical and cognitive development of the pupils. The study recommends increasing the frequency and duration of PE classes, implementing standardized curricula that emphasize fundamental motor skills, and incorporating technology to enhance engagement. It also advocates for the inclusion of culturally relevant activities to boost motivation and participation. Lastly, the study highlights the need for policies that ensure consistent and comprehensive PE programs across schools to promote long-term benefits for pupils' development. There should be further research on how the community influences the pupils’ motor skill development.